IMPLEMENTATION OF SHARIA PRINCIPLES IN MODERN BUSINESS MANAGEMENT IN INDONESIA - Muhammad Fauzi Siregar; Friska Haliza Siregar; M. Guffar Harahap (CV. Barokah Publsiher, 2024)
The rapid development of modern business in Indonesia has created both opportunities and challenges in implementing Sharia principles. As the country with the largest Muslim population in the world, Indonesia has witnessed significant growth in Islamic financial institutions, halal industries, and Sharia-based business practices. This study aims to analyze the implementation of Sharia principles in modern business management in Indonesia, identify the challenges faced by business actors, and examine the opportunities for strengthening Sharia compliance in contemporary business environments. This research employs a library study method by reviewing academic journals, books, government regulations, and previous research related to Sharia business management. The findings indicate that Sharia principles such as justice (adl), transparency, honesty, prohibition of riba, gharar, and maysir, as well as the application of Maqashid Sharia, play an important role in creating ethical and sustainable business practices. However, challenges such as limited Sharia literacy, competition with conventional businesses, and regulatory complexity remain obstacles to implementation. The study concludes that strengthening education, regulation, and technological innovation is necessary to improve Sharia compliance in modern business management.